Preliminary design framework for the power gearbox in a contra-rotating open rotor - San Benito Pastor, Diana Guiomar; Nalianda, Devaiah; Sethi, Vishal; Midgley, Ron; Rolt, Andrew Martin; Block Novelo, David A. (ASME, 2020)
This study introduces an innovative approach to sizing a differential planetary gearbox for a counter-rotating open rotor application. An updated methodology is proposed for the design of maximum load capacity gears based on the power transmitted, durability and space-envelope requirements of the application. The reported methodology has been validated by comparing the results to published data, demonstrating a maximum difference of 0.6% in geometry. Parametric analyses have also been performed to assess the impact of the design assumptions on gearbox dimensional trends. The proposed methodology enables the assessment of the impact of the preliminary transmission system design on engine performance and general arrangement. The characteristics of the gearset lead to an unequal torque split between output shafts (i.e. the propeller shafts). Given the design assumptions made, the study indicates that valid torque ratios would lie between 1.1 and 1.33. The impact of the torque ratio on the size of the gearbox has been analysed for equal rotational speeds and for different speeds between the output shafts. The study established that the transmission system design needs to be considered prior to selection of the torque ratio at engine design level
Keywords: Stress; Propellers; Geometry; Gears; Engines; Engine design; Durability; Torque; Rotors; Mechanical drives; Design